The NOSA-ITACA code for the safety assessment of ancient constructions: A case study in Livorno. (November 2015) - Girardi, M.; Padovani, C.; Pellegrini, D.
Abstract: The present paper describes the main features of the finite element code NOSA-ITACA for the static and dynamic analysis of masonry buildings of historical interest. The code, which models masonry as a nonlinear elastic material with zero tensile strength and bounded compressive strength, is aimed at assessing the static safety and seismic vulnerability of masonry constructions in light of Italian regulations, as well as modelling possible strengthening interventions. The NOSA-ITACA code has been used to study the "Voltone", a large vaulted masonry structure located beneath the "Piazza della Repubblica" square in Livorno. The structure has been analysed in the presence of permanent and accidental loads, calculated on the basis of current Italian regulations. This case study has provided the opportunity to validate the NOSA-ITACA code and highlighted the key role played by numerical tools in assessing the safety of ancient masonry constructions.